The Relationship between Judicial Control of Referendum’s Permissibility and the Sovereignty of the People - Baltrimas, Johanas (Vilnius University Open Series, 2024)
The Supreme Administrative Court of Lithuania has the power to evaluate the legality of the Supreme Electoral Commission’s decisions which recognize referendum initiatives as incompatible with the Constitution. Such decisions bear a significant impact on democratic governance; therefore, the rules that enable it can be considered as competing with the ones that establish the Nation’s sovereignty and the exclusive power of the Constitutional Court to officially interpret the Constitution. The article aims to provide catalysts for the formulation of a doctrine according to which this potential disharmony could be solved by developing constitutional jurisprudence detailing how ordinary courts can interpret and apply the Constitution.
Keywords: Constitutional Law; referendum; constitutional interpretation